HUBUNGAN KOORDINASI MATA DAN TANGAN TERHADAP PUKULAN SERVIS DALAM PERMAINAN TENIS LAPANGAN PADA PUTRI PELTI BAGANSIAPIAPI KECAMATAN BANGKO KABUPATEN ROKAN HILIR - Helmi Niza; Zainur Zainur; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The purpose of this research was to determine eye and hand coordination to service punches in playing tennis on the women's PELTI Bagansiapiapi Bangko District, Rokan Hilir Regency. This research has been carried out at PELTI Bagansiapiapi tennis court, Bangko District, Rokan Hilir Regency and was conducted in November 2019-February 2020, with a total sample of 12 (twelve) people. This study consists of two variables namely the independent and dependent variables. The independent variable (X) is the eye and hand coordination and as the dependent variable (Y) on the results of the tennis service Punch. From the calculation results obtained by simple correlation coefficient (R test) obtained R count = 1.877 while Rtable obtained at 0.735, so R count > R table, meaning that there is a significant relationship between Eye and Hand Coordination (X) with Service Accuracy (Y). Then Ha is accepted.Key Words: Eye and Hand Coordination, Service Punch